Distinct Prognostic Values of Phospholipase C Beta Family Members for Non-Small Cell Lung Carcinoma. (7th April 2019) - Zhang, Tengfang; Song, Xiaowei; Liao, Xiwen; Wang, Xiangkun; Zhu, Guangzhi; Yang, Chengkun; Xie, Xiaoyong
Abstract : Background . Non-small cell lung cancer (NSCLC) is a main cause of cancer-related mortality worldwide. The relationships of the phospholipase C beta (PLCB) enzymes, which are encoded by the genes PLCB1, PLCB2, PLCB3, and PLCB4, with NSCLC have not been investigated. Therefore, the aim of the present study was to identify any correlations between NSCLC prognosis and the expression patterns of PLCB family members. Materials and Methods . The prognostic values of the PLCB gene family members in NSCLC patients were evaluated using the "Kaplan–Meier plotter" database, which includes updated gene expression data and survival information of a total of 1, 926 NSCLC patients. The GeneMANIA plugin of Cytoscape software was used to evaluate the relationships of the four PLCB family members at the gene and protein levels. Gene ontology enrichment analysis and KEGG pathway analysis were performed using the Database for Annotation, Visualization, and Integrated Discovery. Results . High mRNA expression levels of PLCB1, PLCB2, and PLCB3 were significantly associated with poor overall survival (OS) of all NSCLC patients and significantly associated with poor prognosis of adenocarcinoma. In contrast, high mRNA expression of PLCB4 was associated with better OS of adenocarcinoma patients. In addition, the expression levels of the PLCB family members were correlated to smoking status, clinical stage, and patient sex but not radiotherapy and chemotherapy outcomes. Conclusions . PLCB1, PLCB2, PLCB3, and PLCB4 appear to be potential biomarkers for the prognosis of patients with NSCLC. The prognostic values of the PLCB genes require further investigations.